Meningkatkan Aktivitas Dan Hasil Belajar Siswa Pada Muatan IPS Menggunakan Kombinasi Model PBL, GI, Dan NHT - Muhammad Fakhrizan Ikhsan; Tika Puspita Widya Rini (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2024)
The low activity levels and poor social studies content learning outcomes of VA class students at SDN Keraton 1 Martapura inspired this study. The problem in this exploration is that understudies don't comprehend the learning material, the understudies' relational abilities are low, the degree of fearlessness is missing and the capacity to cooperate in bunches is deficient. This review utilized a subjective methodology with the sort of Homeroom Activity Exploration (PTK) which was done for four gatherings. The exploration setting was completed at SDN Keraton 1 Martapura in VA class understudies with a sum of 24 understudies for the 2022/2023 scholarly year. The exploration was led on friendly examinations satisfied with the topic of Our Companions Climate. The sort of information utilized is subjective information as perceptions of educator exercises and understudy exercises in learning exercises as well as quantitative information as understudy learning results got through individual tests. The percentage scale and established indicators of classical learning mastery are used to calculate data analysis. At meeting IV, the results showed that teacher activity scored 31 in the very good category when it combined the Problem-Based Learning, Group Investigation, and Numbered Head Together models. Understudy action scores 91.67% in the extremely dynamic class. understudy learning results are gotten through individual tests with fulfillment coming to 100 percent.